Parenting of Parents with Visual Impairment in Forming Creative Character in Children - Armaini Armaini; Iga Setia Utami; Gaby Arnez; Setia Budi (Edumaspul: Jurnal Pendidikan, 2023)
Shaping a child's creative nature is a challenge in itself for parents with disabilities. Especially if the parents' disability is blindness with visual impairments. With these limitations, blind parents will find it difficult to care for, raise, train, and supervise their children. Therefore, the aim of this research is to find out how blind parents cultivate their children's creative c haracter education. This study uses a qualitative narrative method. The sources of data for this research originate from blind parents and other informants. Data collection techniques include interviews, observation, and documentation. This is what the results of this study show. unique parenting habits for children. This can encourage creative ideas in children, including those whose parents have low vision.